The Impact of Using Learning Media Robot Transporter toward Learning Outcome and Learning Gain of Students - Chandra Ainur Rizki; I Gusti Putu Asto Buditjahjanto; Bambang Suprianto (Journal of Educational Science and Technology (EST), 2020)
This study aims 1) to determine the validity and reliability of the robot transporter learning media instrument, 2) to know the differences in the student learning outcomes between the use of robot transporter and PowerPoint as learning media, and 3) to know how much the learning gain score from the use of these two media. A pre-test-post-test comparison group design type was used. A sample of 60 vocational students participated in two groups, the experimental group (N = 30) and the control group (N = 30).  The results show that the robot transporter learning media is categorized as valid and reliable. The t-test result is 12.589 greater than the t table, namely 2.3596 with a significance of 0.05. Therefore, there is a difference in student learning outcomes. The mean of learning gain score on the robot transporter is 0.694, higher than the mean of learning gain score on the PowerPoint which is 0.289. The use of robot transporter as learning media can help students to be more interactively involved in learning. This is indicated by the students' post-test scores and the value of the gain learning in the experimental class was higher than the control class.